2018
DOI: 10.3389/fmicb.2018.01036
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles From the Helminth Fasciola hepatica Prevent DSS-Induced Acute Ulcerative Colitis in a T-Lymphocyte Independent Mode

Abstract: The complexity of the pathogenesis of inflammatory bowel disease (ulcerative colitis and Crohn’s disease) has led to the quest of empirically drug therapies, combining immunosuppressant agents, biological therapy and modulators of the microbiota. Helminth parasites have been proposed as an alternative treatment of these diseases based on the hygiene hypothesis, but ethical and medical problems arise. Recent reports have proved the utility of parasite materials, mainly excretory/secretory products as therapeuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 74 publications
2
41
0
2
Order By: Relevance
“…Interestingly, in mice treated with EV‐depleted ESP fractions (secreted proteins only), IL‐10 was not elevated but the anti‐inflammatory cytokine TGFβ was increased compared to untreated mice that received TNBS alone, indicating that EVs and soluble ES proteins induce distinct anti‐inflammatory pathways . Similarly, EVs from the zoonotic liver fluke F. hepatica modulate immune responses in dextran sulfate sodium‐induced colitis, resulting in protection which is mediated by other cells distinct from B‐ and T lymphocytes . In this study, reduction in pro‐inflammatory cytokines interfering with both mitogen‐activated protein kinase and NF‐κB pathways was demonstrated.…”
Section: Immunotherapeutic Applications and Evs As Vaccine Targetsmentioning
confidence: 58%
“…Interestingly, in mice treated with EV‐depleted ESP fractions (secreted proteins only), IL‐10 was not elevated but the anti‐inflammatory cytokine TGFβ was increased compared to untreated mice that received TNBS alone, indicating that EVs and soluble ES proteins induce distinct anti‐inflammatory pathways . Similarly, EVs from the zoonotic liver fluke F. hepatica modulate immune responses in dextran sulfate sodium‐induced colitis, resulting in protection which is mediated by other cells distinct from B‐ and T lymphocytes . In this study, reduction in pro‐inflammatory cytokines interfering with both mitogen‐activated protein kinase and NF‐κB pathways was demonstrated.…”
Section: Immunotherapeutic Applications and Evs As Vaccine Targetsmentioning
confidence: 58%
“…A number of parasites have shown to release EVs and they have received great interest due to their remarkable immunomodulatory properties including suppression of IL-6, TNFα, and IL-17A in mice ( 191 , 199 , 200 ). Various potential mechanisms have been suggested through which these vesicles might affect host cells ( 201 ).…”
Section: Evs For the Host Immune Systemmentioning
confidence: 99%
“…E. granulosus secretes EVs that are internalised by dendritic cells enhancing CD86 and MHC II expression on the cell surface [21]. Recently, Roig et al [26] showed that F. hepatica EVs modulate the activity of macrophages and DCs in addition to reducing the severity of DSS-induced colitis in mice suggesting that EVs contain potential biotherapeutic molecules. Many of these vesicles are targeted by antibodies isolated form infected animals [23,27] or animals vaccinated with EVs or EV-surface proteins [23,27] making them important vaccine candidates.…”
Section: Introductionmentioning
confidence: 99%